(untitled) (Eurasian Journal of Philology Science and Education, 2015)
The article considers the peculiarities of translating English brief informational messages into the Russian and English languages. In the last decade significantly increased interest in the study of the versatile features of the translation brief informational messages which are used in the most important areas of our society. These include the means of mass communication and, in particular, the newspaper style. Press is actively involved in shaping public opinion, in creating a specific ideological background in the promotion of various systems of values, and it performs an important social function. The increased attention to the language of newspapers is explained by the fact that the newspaper is a mass medium, which folded and formed the main stylistic devices and tools specific to the language of mass communication, which subsequently influence the development of language in general. Information message as an object of study is of interest to many areas of the science of language: the traditional areas (functional stylistics, semantics, text linguistics, psycholinguistics, sociolinguistics) and new areas (cognitive linguistics, discourse analysis, computer linguo-pragmatics).